2024
DOI: 10.1021/acsomega.3c07312
|View full text |Cite
|
Sign up to set email alerts
|

Flexible Polyurethane Foams Modified with Novel Coconut Monoglycerides-Based Polyester Polyols

Christine Joy M. Omisol,
Blessy Joy M. Aguinid,
Gerson Y. Abilay
et al.

Abstract: Coconut oil, a low-molecular-weight vegetable oil, is virtually unutilized as a polyol material for flexible polyurethane foam (FPUF) production due to the high-molecular-weight polyol requirement of FPUFs. The saturated chemistry of coconut oil also limits its compatibility with widely used polyol-forming processes, which mostly rely on the unsaturation of vegetable oil for functionalization. Existing studies have only exploited this resource in producing low-molecular-weight polyols for rigid foam synthesis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 74 publications
0
7
0
Order By: Relevance
“…These peaks have conspicuously augmented peaks for NSF, indicative of the successful incorporation of the ester- and phenyl-rich coconut oil-based polyol in PU structure. Similarly, the stretching vibration band of C–N at 1537 cm −1 on the spectrum of NSF also has an increased intensity than the peak on the control at 1539 cm −1 owing to the higher OH number of the coconut oil-based polyol, thus forming more urethane linkages 21 .
Figure 1 FTIR spectra comparison of a pristine petroleum-based polyurethane foam (control) against the synthesized natural superoleophilic foam (NSF).
…”
Section: Resultsmentioning
confidence: 98%
See 3 more Smart Citations
“…These peaks have conspicuously augmented peaks for NSF, indicative of the successful incorporation of the ester- and phenyl-rich coconut oil-based polyol in PU structure. Similarly, the stretching vibration band of C–N at 1537 cm −1 on the spectrum of NSF also has an increased intensity than the peak on the control at 1539 cm −1 owing to the higher OH number of the coconut oil-based polyol, thus forming more urethane linkages 21 .
Figure 1 FTIR spectra comparison of a pristine petroleum-based polyurethane foam (control) against the synthesized natural superoleophilic foam (NSF).
…”
Section: Resultsmentioning
confidence: 98%
“…It can be observed that both TG and DTG thermographs of the foam samples reveal a similar thermal behavior with three distinct degradation peaks. The first stage of degradation is observed to occur at around 274 °C for the control PU foam and 278 °C for NSF, owing to the decomposition of urethane linkages 21 , 26 , 27 . A striking difference in the foams’ thermal stability can be observed at the second stage of decomposition, assigned to the degradation of soft segments 28 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…17 This comparison indicates the importance of coconut oil, highlighting its role as a valuable resource material with the capacity to support various applications, such as polyurethane formulations. Moreover, this recognition lays the groundwork for future research into utilizing coconut oil derivatives, such as coconut fatty acid distillate (CFAD), 18 coconut monoglyceride (CMG), 19 or cooking oil wastes, 20 highlighting the importance of exploring coconut oil-based polyols for the production of high-quality rigid foams.…”
Section: Introductionmentioning
confidence: 99%